2012
DOI: 10.1007/s11259-012-9540-z
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral tumor necrosis factor α regulation of adipose tissue metabolism and adipokine gene expression in neonatal pigs

Abstract: The neonatal pig is susceptible to stress and infection, conditions which favor tumor necrosis factor α (TNFα) secretion. This study examined whether TNFα can alter metabolic activity and cytokine gene expression within neonatal pig adipose tissue. Cell cultures were prepared from neonatal subcutaneous adipose tissue using standard procedures. Cultures (5 experiments) were incubated with medium containing (14)C-glucose for 4 h to measure glucose conversion to lipid in the presence of combinations of TNFα (10 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Since the observed reduction was relatively small, some caution must be used in the interpretation. Previous research has demonstrated that TNFα can interfere with insulin mediated glucose metabolism in neonatal porcine adipose tissue [ 17 ], thereby creating an insulin resistant state that is characteristic of adipose tissue inflammation in obesity, diabetes and metabolic syndrome [ 31 ]. The present data suggest that ORM1 does not contribute to adipose tissue inflammation in the pig at the low concentrations tested by stimulating TNFα expression or secretion, despite these same ORM1 concentrations (1 and 10 μg/mL medium) reducing glucose utilization by the tissue in vitro [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the observed reduction was relatively small, some caution must be used in the interpretation. Previous research has demonstrated that TNFα can interfere with insulin mediated glucose metabolism in neonatal porcine adipose tissue [ 17 ], thereby creating an insulin resistant state that is characteristic of adipose tissue inflammation in obesity, diabetes and metabolic syndrome [ 31 ]. The present data suggest that ORM1 does not contribute to adipose tissue inflammation in the pig at the low concentrations tested by stimulating TNFα expression or secretion, despite these same ORM1 concentrations (1 and 10 μg/mL medium) reducing glucose utilization by the tissue in vitro [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNFα can regulate the expression of a number of cytokines within neonatal porcine adipose tissue, including stimulating the expression of the pro-inflammatory cytokines IL6, MIF and MCP [ 17 ]. A reduction in IL6 mRNA level by ORM1 has been previously reported for murine 3T3-L1 adipocytes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations